The approach of the Kenyan criminal justice system to the detention of persons declared not criminally responsible on account of mental disability - Viljoen, Frans (University of Pretoria, 2020)
Mini Dissertation (LLM (Disability Rights in Africa))--University of Pretoria, 2020.